The Role and Importance of Scheduling Construction Production in Modern Conditions (Journal of Architectural Design, 2022)
Modern construction is a very complex dynamic probabilistic system. The complexity of such a system is determined by the interaction of a number of construction, installation, design, research and supply organizations, as well as manufacturing enterprises that employ thousands of people and hundreds of machines and mechanisms. The main purpose of the articles is the creation and scientific substantiation of modern methods, models and mechanisms for scheduling construction production, as a means of improving management and accelerating its intensification and efficiency. The developed models, methods and algorithms make it possible to obtain optimal (or close to optimal) schedules for the implementation of construction projects under various implementation conditions. The resulting economic effect indicates the possibility of introducing these software products in the construction industry to improve management efficiency. Using the methodological foundations developed in the dissertation information technology for modelling and evaluating schedules, creating and using an automated control system allows you to repeatedly apply developments, replicate them and carry out their mass implementation with a significant reduction in labour costs and funds. The results of the research are intended to radically improve the organization and technology of engineering training, planning and management of construction production, accelerating the intensification and increasing its efficiency